Ultrasonographic tools used in the evaluation of the canine spleen: a review - Maronezi, Marjury C.; Feliciano, Marcus A. R.; Simões, Ana Paula R.; Lopes Avante, Michelle; Uscategui, Ricardo A. R. (Revista Colombiana de Ciencias Pecuarias, 2017)
The spleen is one of the most susceptible organs to primary tumours, metastasis, and a wide range of diseases of the hematopoietic system. Therefore, detailed assessment of the spleen is of great importance in veterinary medicine, especially in dogs, due to their economic and sentimental value, and as an experimental model in human medicine. Considering the recent advances in diagnostic imaging in companion animals, this review aims to describe the applicability of acoustic radiation force impulse (ARFI) elastography (qualitative and quantitative), Doppler, and contrast-enhanced ultrasonography for evaluating the spleen in dogs. The ARFI elastography is a recent ultrasound method that can provide reference values and aid in the diagnosis and evaluation of splenic abnormalities routinely encountered in veterinary practice. Conventional ultrasonographyof the spleen combined with haemodynamic analysis by Doppler and contrast enhanced ultrasonography is an important tool in diagnosis and triage.